Knowledge sharing and innovation performance: the mediating role of open innovation - Zan, Fangfang; Leong, Yee Choy; Ismail, Noor Azlin; Chu, Mingyue; Mohammad Saif, Abu Naser; Islam, K. M. Anwarul (John Wiley and Sons, 2023)
The investigation into the performance of small and medium-sized enterprises (SMEs) driven by open innovation has received relatively limited attention in academic research. Businesses can enhance their innovation efforts and develop new products or services by using open innovation strategies to tap into internal expertise or examine external facts. The authors examined the rationales and outcomes of open innovation in SMEs by drawing upon existing theories related to the resource-based and knowledge-based perspectives of firms. A conceptual model was proposed. The hypotheses were tested using Partial Least Squares (PLS). Data collected from 429 SMEs were analyzed using SmartPLS 4. The current research indicates that open innovation serves as a mediator between knowledge sharing and innovation performance, with knowledge sharing exerting a positive influence on open innovation and innovation performance. The findings of this study emphasize the increased opportunities presented by open innovation theory and practice, providing insights into the formulation of strategies for the future development of Chinese SMEs.